Kant, Anti-Supersessionism, and the Holocaust - Wojciech Kozyra (Eidos. A Journal for Philosophy of Culture, 2022)
It is common to accuse Christian supersessionism of responsibility for the Holocaust. This article qualifies this claim by arguing that the theological ideology that directly preceded and aided the Holocaust was unequivocally hostile to this traditional Christian doctrine. It is German neo-Marcionism – which deliberately fought against replacement theology – that provides a direct religious context for the Nazi solution to the Jewish question. Kant appears in this picture as the first modern German Christian who consistently pursued an anti-supersessionist agenda of “purifying” Christianity by radically severing it from its Jewish roots.